(untitled) (Nexo Revista Científica, 2020)
Although urban decay of cities is important and valuable items; they are very vulnerable and unstable against natural disasters and on the other hands they are regarded as cultural capital and compressed buildings that are in fact treasury of social memories, methods of planning and life. The present research with the purpose of focusing on crisis management and describing its indices on revitalization of urban decay structure, examines the effective factors on revitalization of urban decay structure in Jomhouri neighborhood with the approach of crisis management. The research methodology from viewpoint of nature is descriptive- analytical and through comparing the defined indices obtained from theoretical fundamentals, the related data were analyzed by using statistical methods and SPSS software and also it is benefit from Expert Choice software. Through examining the effective factors for prioritizing intervention methods for decay structure the following 5 items based on priority were recognized and classified: Land adjustment of plaques (with final point of 0.79) as first priority, widening roads (with final point of 0.71) as second priority, consolidation of building (with final point of 0.57), reconstruction and granting bonus floor area ratio with points of 0.55 and 0.49 as fourth and fifth priority.